DEBIT AIR DAN MUATAN SUSPENSI SUB DAS BANYUIRANG DAS MALUKA KALIMANTAN SELATAN - Jefri H Simamora; Syarifuddin Kadir; Badaruddin Badaruddin (Jurnal Sylva Scienteae, 2020)
Water discharge is the surface flow rate or volume of water flowing through the point status in units of m³/second. Suspension loads are a part of sediment that moves to float in water, which is carried by the flow of water. This riset aims to determine the magnitude of water discharge and suspension load, the relation between water discharge and water level, the relation between suspension load and water level, the relation between suspension load and water discharge in Banyuirang Sub-watershed, Maluka Watershed, South Kalimantan. The measurement of water discharge is carried out using the Current Meter tool method and the buoy (manually) method. The results obtained are known that in the upstream part of the average water discharge is 2,640 m³/second with a value of the suspension content of 0.004 gr/ltr and sediment load of 0.00139 tons/year. In the Middle part the average water discharge is 5,630 m³/second with a suspension value of 0,004 gr/ltr and sediment load of 0,00375 tons/year. In the lower reaches of the average water discharge is 11.723 m³/second with a value of 0.002 suspension levels and a sediment load of 0.004014 tons/year.Keywords: water discharge; suspension load